The Implementation of 2013 Curriculum In Nurul Huda Islamic Senior High School Tangerang - Durotunnasihah Durotunnasihah (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2019)
The research is intended to analyze the process of curriculum development in Nurul Huda Islamic Senior High School. The research is qualitative research. In collecting data, the researcher uses observation and Interview. The result shows that Nurul Huda Islamic Senior High School as an Islamic institution developes the curriculum by using Qur’an and Hadits as base of every activity including teaching and learning. All students do not only learn science as common as the other students in other schools do, but also many religious subjects are taught and learnt. The main purposes of balancing religious subjects and sciences are because the students that have graduated were hoped to become a well-attitude person with the high quality of science.